PENGUATAN LITERASI DIGITAL MELALUI PEMBUATAN MEDIA PEMBELAJARAN BERBASIS VIDEO ANIMASI MENGGUNAKAN ARTIFICIAL INTELLIGENCE BAGI GURU SDN 01 TUGUREJO, KOTA SEMARANG - Ana Putri Nastiti; Isnaini Nurkhayati; Winarto Winarto; Jumi Jumi; Sri Marhaeni; Endang Sulistiyani; Jati Nugroho; Mona Inayah Pratiwi (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2025)
Primary Community Service at SDN 01 Tugurejo, Tugurejo District, Semarang City aims to provide solutions to social and humanities problems that impact performance, efficiency and work productivity faced by teachers at SDN 01 Tugurejo in order to improve the quality of learning. The problem faced by teachers at SDN 01 Tugurejo, Semarang City is that they have not yet maximized good digital literacy skills. In particular, teachers have not been able to apply technology optimally in creating learning media that is relevant to students' characters and the latest technological developments. The application of Artificial Intelligence through the creation of animated video-based learning media for teachers at SDN 01 Tugurejo will have an impact on strengthening digital literacy for teachers. In an independent curriculum, teachers have the freedom to adapt learning methods, materials and media to suit the needs and characteristics of students. Thus, teachers who have good digital literacy will support the creation of an interactive and quality learning process. The method used is to provide socialization, training and assistance in creating animated video-based learning media using Artificial Intelligence. Thus, teachers who have good digital literacy will support the creation of an interactive and quality learning process.